2007
DOI: 10.1093/hmg/ddm227
|View full text |Cite
|
Sign up to set email alerts
|

The DNA polymerase   Y955C disease variant associated with PEO and parkinsonism mediates the incorporation and translesion synthesis opposite 7,8-dihydro-8-oxo-2'-deoxyguanosine

Abstract: Mitochondrial DNA is replicated and repaired by DNA polymerase gamma (pol gamma), encoded by the POLG gene. The Y955C substitution in POLG leads to autosomal dominant progressive external ophthalmoplegia (PEO) with other severe phenotypes. PEO patients with this mutation can further develop parkinsonism or premature ovarian failure. Mouse and yeast models with this mutation show enhanced amounts of oxidative lesions and increased mtDNA damage. In DNA pol gamma, Tyr955 plays a critical role in catalysis and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 68 publications
5
69
3
Order By: Relevance
“…The mutation causes Pol␥ incorporation levels to drop below 1% of control activity, yet the life span of these patients is measured not in days or weeks but rather in decades, and the individuals are often symptomless well into adulthood. This and other similar mutations in Pol␥ that cause nearly complete loss of protein activity with adult onset of symptoms (62) suggest the presence of a backup polymerase function in the absence of Pol␥.…”
Section: Discussionsupporting
confidence: 57%
“…The mutation causes Pol␥ incorporation levels to drop below 1% of control activity, yet the life span of these patients is measured not in days or weeks but rather in decades, and the individuals are often symptomless well into adulthood. This and other similar mutations in Pol␥ that cause nearly complete loss of protein activity with adult onset of symptoms (62) suggest the presence of a backup polymerase function in the absence of Pol␥.…”
Section: Discussionsupporting
confidence: 57%
“…Graziewicz et al reported that oxidative DNA lesions block mtDNA replication in vitro, which may result in mtDNA depletion [32]. Depletion of damaged mtDNA could explain the scarcity of oxidative mutations in the AZT mutational spectra.…”
Section: Discussionmentioning
confidence: 99%
“…4 With longer disease duration, mtDNA deletions and mutations accumulate, and eventually lead to neuronal death in selectively vulnerable regions in mitochondrial dysfunction such as basal ganglia and cerebellum. 5 In POLG, Y955 specifically plays a critical role in catalysis and fidelity of DNA synthesis, 6 and it is highly conserved in different species. 4,6 POLG mutations can lead to wide-variable clinical presentations.…”
Section: Sectionmentioning
confidence: 99%
“…5 In POLG, Y955 specifically plays a critical role in catalysis and fidelity of DNA synthesis, 6 and it is highly conserved in different species. 4,6 POLG mutations can lead to wide-variable clinical presentations. The age at disease onset varied from 3 months to 66 years.…”
Section: Sectionmentioning
confidence: 99%